The role of agricultural marketing in improving the marketing efficiency and effectiveness of citrus crops in Lattakia Governorate (Field study) - رزوق, صفاء (Latakia University Journal -Biological Sciences Series, 2025)
The study aimed to determine the role of the elements of the agricultural marketing mix (Citrus products, citrus pricing, citrus distribution, citrus promotion) in the marketing efficiency and effectiveness of citrus crops in Lattakia, and to determine the level of marketing efficiency and effectiveness of citrus crops in Lattakia Governorate. The researcher relied on the deductive approach, and relied on the descriptive method to describe the research variables and analyze them based on the primary data that were collected, as the researcher conducted a field study on citrus farmers in Lattakia Governorate to collect the necessary primary data, and the variables were measured on all the primary data that were collected through a questionnaire that was designed by the researcher's review of previous studies and literature, and in order to test the hypotheses, the researcher unloaded the primary data into a database that was analyzed using the SPSS program, version //20. The study reached a number of results, including: The correlation coefficient between agricultural marketing and marketing efficiency and effectiveness of citrus crops was 0.418, which indicates a weak correlation between agricultural marketing and marketing efficiency and effectiveness of citrus crops, which was confirmed by the sub-hypotheses. The results of the study indicate that agricultural marketing of citrus fruits is very important for him and for the farmer; as agricultural marketing plays a major role in the efficiency and effectiveness of citrus marketing. The results of the study also indicate that the citrus product, citrus pricing, citrus distribution, and citrus promotion affect the efficiency and effectiveness of citrus marketing, which was evident in the context of the study.